Faktor-Faktor yang Berpengaruh terhadap Hasil-Hasil Belajar Bahasa Inggris Siswa SMP - Eri Setyowati (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The research aimed to analyze the factors affecting on the English learning outcomes students of Junior High School in Yogyakarta Municipality either partially or in a group. The affecting factors were home environment, learning styles, language learning strategies and prior knowledge. The research was quantitative research using the ex-post facto method. The sampling technique used was the proportional stratified random sampling technique. The data were collected through a questionnaire and score documentation. The data were analyzed by using regression analysis with SPSS 17.00 for windows.